Interplay Between Skin Microbiota Dysbiosis and the Host Immune System in Psoriasis: Potential Pathogenesis - Liang, Xiaoqian; Ou, Caixin; Zhuang, Jiayi; Li, Jinsheng; Zhang, Fangfei; Zhong, Yuanqiu; Chen, Yongfeng (Frontiers in Immunology, 2021)
Psoriasis is a multifactorial immune-mediated disease. The highly effective and eligible treatment for psoriasis is limited, for its specific pathogenesis is incompletely elucidated. Skin microbiota is a research hotspot in the pathogenesis of immune-mediated inflammatory skin diseases nowadays, and it may have significant involvement in the provocation or exacerbation of psoriasis with broadly applicable prospects. It is postulated that skin microbiota alternation may interplay with innate immunity such as antimicrobial peptides and toll-like receptors to stimulate T cell populations, resulting in immune cascade responses and ultimately psoriasis. Achieving a thorough understanding of its underlying pathogenesis is crucial. Herein, we discuss the potential immunopathogenesis of psoriasis from the aspect of skin microbiota, in an attempt to yield insights for novel therapeutic and preventive modalities for psoriasis.